2020
DOI: 10.5123/s1679-49742020000200020
|View full text |Cite
|
Sign up to set email alerts
|

A distribuição espacial e a tendência temporal de recursos humanos para o Sistema Único de Saúde e para a Saúde Suplementar, Brasil, 2005 a 2016*

Abstract: Objective: to analyze the spatial distribution and temporal trend of human resources for the Brazilian National Health System (SUS) and the Supplemental Health sector. Methods: an ecological study was conducted in the country's 27 Federative Units (FUs); SUS Information Technology Department (DATASUS) data were used relating to the doctor, dental surgeon, nurse and nursing technician personnel categories for the period 2005-2016; Prais-Winsten regression was used to assess the time trend. Results: there was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 21 publications
1
11
0
8
Order By: Relevance
“…Another key-disparity is the distribution of HCWs between public and private systems. A study indicated that there is a rising trend for physicians and nurses in the private health insurance sector than in the public health system in Brazil from 2005 to 2016; moreover, the states with the lowest increasing trends for physicians are in the less developed regions of the country (North and Northeast), mostly due to lack of infrastructure in health facilities and few professional training institutions 27 . Other studies have also highlighted the shortage of speciality services as one of the main concerns in SUS, leading to unmet demand, long waiting lists, delay in diagnosis and poor prognosis 10 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Another key-disparity is the distribution of HCWs between public and private systems. A study indicated that there is a rising trend for physicians and nurses in the private health insurance sector than in the public health system in Brazil from 2005 to 2016; moreover, the states with the lowest increasing trends for physicians are in the less developed regions of the country (North and Northeast), mostly due to lack of infrastructure in health facilities and few professional training institutions 27 . Other studies have also highlighted the shortage of speciality services as one of the main concerns in SUS, leading to unmet demand, long waiting lists, delay in diagnosis and poor prognosis 10 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…A cirurgia de varizes é realizada em todas as regiões do país, sendo um procedimento disponibilizado pelo SUS nos principais hospitais regionais e naqueles com capacidade para a realização desse serviço, seguindo seus princípios e diretrizes 9,10 . Portanto, é um procedimento de suma importância, uma vez que a insuficiência venosa crônica pode levar à formação de úlceras de difícil cicatrização com possibilidade de complicações irreparáveis 12 .…”
Section: Discussionunclassified
“…Apesar da importância epidemiológica de se conhecer a distribuição dessa doença, há poucos estudos analisando o perfil das cirurgias de varizes, principalmente no Brasil 1,5,11,12 , um país de vasta extensão territorial e com distribuição desigual da assistência médica especializada. Além disso, não há um trabalho epidemiológico com recorte temporal que englobe todos os procedimentos realizados para o tratamento de varizes na rede pública de saúde de modo a demonstrar as lacunas de assistência médica para essa doença.…”
Section: Introductionunclassified
“…Added to this disparity between the use of IVC filter in Brazil, a developing country with a relatively young publicly funded health system facing underfunding (20), and in developed countries as the USA and the European countries mentioned above, we observed an internal inequality, among Brazilian regions. For instance, in 2019, the rate of IVC filter placement in the South, a richer and more developed region (21), was 20 times higher than in the North, the region with the lowest rates of IVC filter placements, which is also the region with the worst development indexes (21), facing the greatest shortage of health professionals and facilities (22), and with the lowest population density (21) and difficult access to health care. Both these external and internal discrepancies underline that cultural and socioeconomic factors may have impact on the placement of IVC filters, which is in line with other reports (10,14).…”
Section: Ivc Filter Placement Ratesmentioning
confidence: 99%